Connecting Mathematics Education to my Relationship with the Cosmos - Varghese, Jiju (Journal of Transformative Praxis, 2020)
I believe that human beings are closely interconnected to the cosmos in which we exist. Today, we hear a lot about caring for the Mother Earth. More and more humans are coming to realize the need to protect our environment and to stop the uncontrolled exploitation of the nature. With the exploration of the space, we have also come to understand that we are only a tiny particle in this vast cosmos. As a result, we are responsible towards the cosmos that surrounds us and in which we are part of. Often mathematics teaching-learning has been limited to the cognitive level and very seldom concerns of the ecology and issues related to the cosmos are brought up in mathematics classrooms. My mathematics teaching-learning life was no exception as there was hardly any connection to my relationship with the cosmos. Through this autoethnographic study, I show how mathematics teaching-learning needs to and can take into consideration the important relationship and responsibility we have towards the environment, universe and the cosmos and how we can teach pro-cosmological behaviours to our students through topics in mathematics they are learning. This will be done by narrating my lived experiences of missing the link with the cosmos in my mathematics classrooms both as a student and a teacher and by presenting a few examples of making mathematics teaching-learning cosmologically responsible in classrooms.